2022
DOI: 10.3389/fpubh.2022.826911
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Stress and Coping Associated With Mental, Behavioral, and Internet Use Problems Among Adolescents During the COVID-19 Pandemic: A Stratified Random Sampling and Cluster Analysis

Abstract: BackgroundAdolescents are vulnerable to behavioral and mental health problems, which might be further exacerbated during the COVID-19 pandemic. This study explored how participants with different profiles of stressful life events, coping resources (i.e., self-esteem and perceived social support) and coping strategies (i.e., maladaptive and adaptive coping) varied in the prevalence of mental, behavioral, and Internet use problems.MethodsData were collected from a large and representative sample of Chinese secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
(57 reference statements)
1
2
0
Order By: Relevance
“…Similarly, recent data confirm three groups of adolescents whose mental health improved (34%), remained stable (46%), or worsened (15%) during the pandemic compared to pre-pandemic rates [62]. Our findings also partially confirm the study of She et al [63], who also identified three clusters of adolescents in relation to coping during the pandemic, measuring levels of fear of COVID-19, resilience, and smartphone use. In our sample, however, the percentages of students in Clusters 2 (average) and 3 (vulnerable and distressed) were larger.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, recent data confirm three groups of adolescents whose mental health improved (34%), remained stable (46%), or worsened (15%) during the pandemic compared to pre-pandemic rates [62]. Our findings also partially confirm the study of She et al [63], who also identified three clusters of adolescents in relation to coping during the pandemic, measuring levels of fear of COVID-19, resilience, and smartphone use. In our sample, however, the percentages of students in Clusters 2 (average) and 3 (vulnerable and distressed) were larger.…”
Section: Discussionsupporting
confidence: 89%
“… 32 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 Among these studies, 43 were included in the meta-analytical process, for a total of around 65 million subjects (suicides: 63,120,235; suicidal behaviors: 934,951; suicidal ideation: 156,234): two reporting rates of deaths for suicides, 48 , 50 26 reporting prevalence data about suicidal behaviors 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 <...…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies conducted during the pandemic reveal a rising trend in clinically heightened anxiety symptoms over time among adolescents, aligning with concerns about COVID-19′s effects on this demographic [ 6 , 17 , 18 ]. At the same time, it has been pointed out that not all young people showed a deterioration in their psychological health during the pandemic [ 19 , 20 , 21 ]. Therefore, long-term, accurate monitoring to identify risk and resilience factors associated with different mental health paths has gained importance.…”
Section: Introductionmentioning
confidence: 99%